Time-dependent bladder tissue regeneration using bilayer bladder acellular matrix graft-silk fibroin scaffolds in a rat bladder augmentation model. (1st September 2015) - Zhao, Yang; He, Yi; Guo, Jian-hua; Wu, Jia-sheng; Zhou, Zhe; Zhang, Ming; Li, Wei; Zhou, Juan; Xiao, Dong-dong; Wang, Zhong; Sun, Kang; Zhu, Ying-jian; et al.
Graphical abstract: Abstract: With advances in tissue engineering, various synthetic and natural biomaterials have been widely used in tissue regeneration of the urinary bladder in rat models. However, reconstructive procedures remain insufficient due to the lack of appropriate scaffolding, which should provide a waterproof barrier function and support the needs of various cell types. To address these problems, we have developed a bilayer scaffold comprising a porous network (silk fibroin [SF]) and an underlying natural acellular matrix (bladder acellular matrix graft [BAMG]) and evaluated its feasibility and potential for bladder regeneration in a rat bladder augmentation model. Histological (hematoxylin and eosin and Masson's trichrome staining) and immunohistochemical analyses demonstrated that the bilayer BAMG-SF scaffold promoted smooth muscle, blood vessel, and nerve regeneration in a time-dependent manner. At 12 weeks after implantation, bladders reconstructed with the BAMG-SF matrix displayed superior structural and functional properties without significant local tissue responses or systemic toxicity. These results demonstrated that the bilayer BAMG-SF scaffold may be a promising scaffold with good biocompatibility for bladder regeneration in the rat bladder augmentation model.